New genera and species of brachypterous members of the tribe Meconematini (Orthoptera: Tettigoniidae) from Hunan, China - Xin, Yarui; Wang, Tao; Shi, Fuming (Zootaxa, 2020)
In the paper, 2 new genera and 2 new species of Meconematinae in Tettigoniidae are described from southern Hunan, China, i.e. Xiangothaumaspis Xin, Wang & Shi gen. nov., Xiangothaumaspis falcatus Xin, Wang & Shi sp. nov.; Neocosmetura Xin, Wang & Shi gen. nov., Neocosmetura torcha Xin, Wang & Shi sp. nov., and the characteristic photographs are provided.